Predictors of adherence to influenza vaccination for healthcare workers from a teaching hospital: a study in the prepandemic era - Cavalcante, Ricardo de Souza [UNESP]; Zambonatto Jorge, Aline Maia [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP] (Soc Brasileira Medicina Tropical, 2010)
Introduction: Even before the 2009 pandemics, influenza in healthcare workers (HCW) was a known threat to patient safety, while Influenza vaccine coverage in the same group was generally low. Identification of predictors for HCW adherence to Influenza vaccination has challenged infection control committees. Methods: Our group conducted a cross-sectional survey in December 2007, interviewing 125 HCWs from a teaching hospital to identify adherence predictors for Influenza vaccination. The outcomes of interest were: A - adherence to the 2007 vaccination campaign; B - adherence to at least three yearly campaigns in the past five years. Demographic and professional data were assessed through univariate and multivariate analysis. Results: of the HCWs interviewed, 43.2% were vaccinated against Influenza in 2007. However, only 34.3% of HCWs working in healthcare for more than five years had adhered to at least three of the last five vaccination campaigns. Multivariate analysis showed that working in a pediatric unit (OR = 7.35, 95% I = 1.90-28.44, p = 0.004) and number of years in the job (OR = 1.32, 95%CI = 1.00-1.74, p = 0.049) were significant predictors of adherence to the 2007 campaign. Physicians returned the worst outcome performances in A (OR = 0.40, 95%CI = 0.16-0.97, p = 0.04) and B (OR = 0.17, 95%CI = 0.05-0.60, p = 0.006). Conclusions: Strategies to improve adherence to Influenza vaccination should focus on physicians and newly-recruited HCWs. New studies are required to assess the impact of the recent Influenza A pandemics on HCW-directed immunization policies.

INTRODUÇÃO: Mesmo antes da pandemia de 2009, o acometimento de profissionais da área da saúde (PAS) pela influenza já era uma ameaça conhecida para pacientes internados. A cobertura vacinal desse grupo era geralmente baixa. A identificação de preditores de adesão de PAS à vacinação contra influenza é um desafio para Comissões de Controle de Infecção. MÉTODOS: Realizou-se estudo transversal em Dezembro de 2007, entrevistando 125 PAS de um hospital de ensino para identificar preditores de adesão à vacinação contra influenza. Os desfechos de interesse foram: A - adesão à campanha de 2007; B - adesão a pelo menos três campanhas nos últimos cinco anos. Dados demográficos e profissionais foram analisados em modelos univariados e multivariados. RESULTADOS: Dos entrevistados, 43,2% haviam sido vacinados em 2007. No entanto, apenas 34,3% daqueles trabalhando há mais de cinco anos aderiram a três ou mais campanhas nesse período. Análise multivariada demonstrou que trabalhar em enfermaria pediátrica (OR = 7.35, 95% CI = 1.90-28.44, p = 0,004) e o número de anos no emprego (OR = 1.32, 95% CI = 1.00-1.74, p = 0.049) foram preditores significantes de adesão em 2007. Médicos tiveram má performance nos desfechos A (OR = 0,40, 95% CI = 0.16-0.97, p = 0,04) e B (OR = 0,17, 95% CI = 0,05-0,60, p = 0,006). CONCLUSÕES: Estratégias para aumentar adesão à vacinação contra influenza devem priorizar médicos e PAS admitidos recentemente ao emprego. Novos estudos são necessários para abordar o impacto da recente pandemia de influenza sobre as políticas de vacinação para PAS.
Preditores de adesão à vacinação contra influenza em profissionais de um hospital de ensino: um estudo na era pré-pandêmica
Keywords: Influenza; Vaccination; Healthcare workers